2018
DOI: 10.1038/nrneph.2017.188
|View full text |Cite
|
Sign up to set email alerts
|

Kidneys and women's health: key challenges and considerations

Abstract: The theme of World Kidney Day 2018 is 'kidneys and women's health: include, value, empower'.To mark this event, Nature Reviews Nephrology asked four leading researchers to discuss key considerations related to women's kidney health, including specific risk factors, as well as the main challenges and barriers to care for women with kidney disease and how these might be overcome. They also discuss policies and systems that could be implemented to improve the kidney health of women and their offspring and the are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 64 publications
1
12
0
3
Order By: Relevance
“…Thus, kidney disease has evolved from a subspeciality concern to a global health problem [1,2]. More recently, the scientific community has become increasingly aware of sex-specific influences on the incidence and progression of renal disorders [3]. Worldwide, it has been reported that the proportion of women with earlier stages of CKD is higher than that of men.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, kidney disease has evolved from a subspeciality concern to a global health problem [1,2]. More recently, the scientific community has become increasingly aware of sex-specific influences on the incidence and progression of renal disorders [3]. Worldwide, it has been reported that the proportion of women with earlier stages of CKD is higher than that of men.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that imprecise estimation of renal function in women and gender bias in the approach to ESKD care (including approach to and barriers precluding timely access to transplant wait‐listing and subsequent transplantation) are operative . Identifying potential modifiable factors is urgently needed to better understand and reduce this sex disparity in the management of women with ESKD …”
Section: Sex Disparitymentioning
confidence: 99%
“…Differences in the manifestation of illness and the experience of symptoms between men and women have been increasingly acknowledged (Ashuntantang et al, 2018;Barsky et al, 2001). 'Sex differences' generally refer to differing biological characteristics between males and females.…”
Section: Sex and Gender Differences In The Manifestation And Experience Of Symptomsmentioning
confidence: 99%